INTENSIFIKASI PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI WILAYAH SINGOSARI (Studi Penelitian pada Unit Pelaksana Teknis Daerah (UPTD) Dinas Pendapatan Singosari) - Aditma, Ferta Ayu (Jurnal Mahasiswa Perpajakan, 2014)
The Purpose of this study is to describe how the Unit Pelaksana Teknis Daerah (UPTD) distributes information about land tax to societies and to explain how the fiscus provides services related to the societies tax payment. The study also aims to illustrate what activities conducted by the fiscus to gain trust from the tax payers. The study was conducted in January 2014 in the UPTD. It applied street observation and interview to both the fiscus and the tax payer. The finding show that the UPTD intensifies incomes from land tax by using several activities: providing information (penyuluhan), improving administration services (pelayanan), checking documents to examine tax payers compliance (pemeriksaan). Those activities are categorized as psychological aspects, while they also do other activities in legal aspects. The UPTD distributes information about land tax by using baliho, internet and socialization. Service provided by the UPTD include the improvements of quality and capability employees, infrastructure improvements, visiting tax payer’s homes (door to door) and lengthening working days.Keywords: intensification of Land Tax Collection, communication and information transfer, service, the trust of Taxpayer to fiscus